IMPROVING OF TAX LITERACY OF RUSSIAN POPULATION IN TERMS OF DIGITALIZATION OF THE ECONOMY - Aleksandrova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents an overview of the concept of tax literacy as the main element of financial literacy and the necessary prerequisite for the formation of the tax culture of society and the individual. The expansion of the field of knowledge and skills that form the tax literacy of the population in the era of the digital economy is shown.The aim of the study is to analyze the prerequisites for the formation and development of tax literacy in the Russian Federation and its impact on improving the efficiency of the tax system. The study used traditional methods of scientific research, the monographic method, and the method of comparative analysis.The results of a comparative analysis of the level of financial literacy in different countries showed the insufficiency of its development in Russia. Based on the analysis of the state of taxation of individuals in the Russian Federation, the problems of the formation of tax literacy and tax culture of the population of Russia are identified, for the solution of which the author formulated proposals.